Uncovered Interest Parity - Isard, Peter (Washington, D.C. : International Monetary Fund, 2006)
This paper provides an overview of the uncovered interest parity assumption. It traces the history of the interest parity concept, summarizes evidence on the empirical validity of uncovered interest parity, and discusses different interpretations of the evidence and the implications for macroeconomic analysis. The uncovered interest parity assumption has been an important building block in multiperiod models of open economies, and although its validity is strongly challenged by the empirical evidence, at least at short time horizons, its retention in macroeconomic models is supported on pragmatic grounds by the lack of much empirical support for existing models of the exchange risk premium.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet